2015
DOI: 10.5539/gjhs.v8n4p10
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Perennial Kitchen Garden Model to Improve Diet Diversity in Melghat, India

Abstract: Lack of diet diversity causing micronutrient deficiency is common in developing countries and is gaining attention due to the hidden consequences of impaired physical and cognitive development. This paper describes the propagation of a sustainable perennial kitchen garden (KG) model to address household (HH) diet diversity in Melghat. Nutrient dense plants, comprising of minimum one tree (perennial) and one green leafy vegetable (GLV) were given to participating HHs along with qualitative interventions. Baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Across included reviews, 24 unique primary garden-based intervention studies met inclusion criteria [ 14 , 24 , 25 , 62 82 ] and were published between 1991 [ 70 ] and 2017 [ 25 ]. Most garden-based interventions ( n = 15) were implemented in the home [ 24 , 25 , 64 , 67 – 71 , 73 – 77 , 82 ] and 8 were conducted in school, afterschool, or early care and education settings [ 14 , 63 , 65 , 66 , 78 81 ]. Only one community garden-based intervention included our age group of interest [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across included reviews, 24 unique primary garden-based intervention studies met inclusion criteria [ 14 , 24 , 25 , 62 82 ] and were published between 1991 [ 70 ] and 2017 [ 25 ]. Most garden-based interventions ( n = 15) were implemented in the home [ 24 , 25 , 64 , 67 – 71 , 73 – 77 , 82 ] and 8 were conducted in school, afterschool, or early care and education settings [ 14 , 63 , 65 , 66 , 78 81 ]. Only one community garden-based intervention included our age group of interest [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous study reported male babies are less likely to have LBW, compared to their female counterparts because the male chromosome confers advantages in the determination of birth weight [ 51 ]. Interestingly, having access to a kitchen garden at home provides opportunities to increase dietary diversity and consume green leafy vegetables during pregnancy [ 52 ]. This study also revealed that mothers in the intervention area were found to be at a lower risk of having an LBW baby, indicating the beneficial effects of MATRI-SUMAN intervention [ 23 ] in lowering LBW cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is against this background that we propose the use of on-farm diversity as a more relevant measure of production diversity. We distinguish it from field-level production diversity by bringing in 2 additional activities that supplement a household's agricultural production: kitchen garden 16,17 and livestock rearing. Furthermore, we retain plot-level cultivation of pulses and vegetables.…”
Section: Introductionmentioning
confidence: 99%